2014
DOI: 10.1016/j.bbalip.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent binding of wild-type lipoprotein lipase (LPL) and S447X-LPL to GPIHBP1, the endothelial cell LPL transporter

Abstract: The S447X polymorphism in lipoprotein lipase (LPL), which shortens LPL by two amino acids, is associated with low plasma triglyceride levels and reduced risk for coronary heart disease. S447X carriers have higher LPL levels in the pre- and post-heparin plasma, raising the possibility that the S447X polymorphism leads to higher LPL levels within capillaries. One potential explanation for increased amounts of LPL in capillaries would be more avid binding of S447X-LPL to GPIHBP1 (the protein that binds LPL dimers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Another study showed that ANGPTL4 displaces LPL from GPIHBP1 35 . Although GPIHBP1 bound equivalently to LPL and LPL S447X , it is possible that GPIHBP1 differently protects LPL and LPL S447X from inhibition by ANGPTL4 11 . We therefore tested the protective effect of GPIHBP1 on LPL and LPL S447X inhibition by ANGPTL4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that ANGPTL4 displaces LPL from GPIHBP1 35 . Although GPIHBP1 bound equivalently to LPL and LPL S447X , it is possible that GPIHBP1 differently protects LPL and LPL S447X from inhibition by ANGPTL4 11 . We therefore tested the protective effect of GPIHBP1 on LPL and LPL S447X inhibition by ANGPTL4.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of proteins in tissue culture media showed that LPL S447X had increased 9 , decreased 8, 10 , or no difference 11, 12 in activity. Many of these studies used LPL quantified by ELISA to determine protein mass, whereas others use Western blots.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…To understand the role of LPL in intravascular lipolysis, the field will ultimately need to define the effects of apo-AV, apo-CII, apo-CIII, and ANGPTL4 on GPIHBP1-bound LPL. Similarly, in order to understand the effects of various LPL polymorphisms ( e.g., the S447X polymorphism) on LPL activity, it will be important to study the effect of the polymorphism on GPIHBP1-bound LPL [29]. …”
Section: Gpihbp1 Transports Lpl To the Capillary Lumenmentioning
confidence: 99%
“…30 A metaanalysis on previous studies among adults showed that S447X polymorphism decreased TG and increased HDL-C, and therefore decreased the CVD risk. 32 The key role of LPL is in postprandial lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%